Can people experience post-traumatic growth after committing violent acts? - Blackie, Laura E.R.; Roepke, Ann Marie; Hitchcott, Nicki; Joseph, Stephen (American Psychological Association, 2016)
The concept of post-traumatic growth refers to the positive psychological changes that some people experience as a result of their struggle with highly stressful and often traumatic circumstances. Research into post-traumatic growth has typically focused on survivors of violent victimisation or other uncontrollable and tragic circumstances. However, emerging research into service members in the armed forces has shown that post-traumatic growth can also occur in this population. We synthesise existing research to propose a preliminary model outlining the psychosocial processes that may facilitate post-traumatic growth among people who have perpetrated acts of violence. We end by discussing some of the important questions that future theoretical and empirical work will need to address.